ANALISIS PENGARUH FASILITAS WISATA DAN JARAK PERJALANAN TERHADAP TINGKAT KUNJUNGAN WISATAWAN DI TAMAN MARGASATWA BUDAYA KINANTAN KOTA BUKITTINGGI - Cesa Vircilia Thomas; Novera Martilova (Jurnal Ekonomi dan Bisnis, 2023)
This study aims to determine the effect of tourist facilities and travel distance on the level of tourist visits at the Kinantan Cultural Wildlife Park, Bukittinggi City. This research can be used to increase further tourist visits. The type of research used in this research is descriptive quantitative research with a quantitative approach and a type of field research using a questionnaire and a total sample of 100 respondents. And with data analysis methods used validity, reliability, classical assumptions (normality test, autocorrelation test, multicollinearity test, heteroscedasticity test), multiple linear regression test, R² coefficient of determination test and hypothesis testing (t test, f test). The results of this study indicate that the multiple linear regression test for tourist facilities has a value of 0.260 if every 1 percent increase in the tourism facility variable will affect the level of tourist visits by 0.260 (26%) and travel distance has a value of 0.848 if every 1 percent increase in the travel distance variable, it will affect the level of tourist visits by 0.848 (84.8%). Then, the Sig value t test for the influence of tourist facilities on visit rates is 0.039 <0.05 and the t value is 2.093 > 0.677. The Sig value for the effect of travel distance on the visit rate is 0.000 <0.05 and the tcount is 5.909 > 0.677. This shows that H1 and H2 are accepted. And the results of the R² test obtained a value of 0.585 or 58.5%. Which proves that how much the Independent variable can explain the Dependent variable with a figure of 58.5% and the remaining 41.5% is explained by other variables. Based on the f test of the influence of tourist facilities and travel distance simultaneously the visit rate is 0.000 <0.05 and the calculated f value is 68.455 > f table 3.09.